Aqueous Manufacturing of Defect-Free Thick Multi-Layer NMC811 Electrodes - Lukas Neidhart; Katja Fröhlich; Nicolas Eshraghi; Damian Cupid; Franz Winter; Marcus Jahn (Nanomaterials, 2022)
Manufacturing thick electrodes for Li-ion batteries is a challenging task to fulfill, but leads to higher energy densities inside the cell. Water-based processing even adds an extra level of complexity to the procedure. The focus of this work is to implement a multi-layered coating in an industrially relevant process, to overcome issues in electrode integrity and to enable high electrochemical performance. LiNi<semantics>0.8</semantics>Mn<semantics>0.1</semantics>Co<semantics>0.1</semantics>O<semantics>2</semantics> (NMC811) was used as the active material to fabricate single- and multi-layered cathodes with areal capacities of 8.6 mA h cm−2. A detailed description of the manufacturing process is given to establish thick defect-free aqueous electrodes. Good inter-layer cohesion and adhesion to the current collector foil are achieved by multi-layering, as confirmed by optical analysis and peel testing. Furthermore, full cells were assembled and rate capability tests were performed. These tests show that by multi-layering, an increase in specific discharge capacity (e.g., 20.7% increase for C/10) can be established for all tested C-rates.